Peran Kader Posyandu dalam Pemeriksaan Kesehatan Balita di Dusun Sungai Belit Desa Sejahtera Kecamatan Sukadana Kabupaten Kayong Utara - Hikmah, Dinda Mutiara (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
This research aims to determine the factors that limit parental involvement in children's health checks at Posyandu Sakura Putih, as well as the role of Posyandu cadres in improving the health of children under five at that location. The research was conducted in Sungai Belit Hamlet, Sejahtera Village, Sukadana District, North Kayong Regency, using a qualitative descriptive research method involving parents, village midwives and posyandu cadres. Research findings identified three main barriers related to parental involvement, namely lack of information about the importance of health checks, limited posyandu facilities, and lack of government supervision. Meanwhile, the role of posyandu cadres includes health checks for toddlers, dissemination of health information, home visits and health education to the community to increase awareness and understanding of children's health.